2017
DOI: 10.1590/s1806-92902017000500010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fermented fish meal supplementation on growth performance, blood metabolites, and fecal microflora of weaning pigs

Abstract: -This study was conducted to estimate the effect of dietary supplementation with fermented fish meal on growth performance, blood metabolites, and fecal microflora in weaning pigs. A total of 180 weaned pigs ((Landrace × Yorkshire) × Duroc; with average body weight of 6.0 kg) were randomly distributed among three dietary treatments (0, 0.2, and 0.5% fermented fish meal) in three replicate pens (20 heads per pen) in a completely randomized trial over three weeks. Addition of fermented fish meal to weanling pig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…A further study is needed to clarify the adverse effect of long-term storage of PFR before use in livestock feed. A previous study revealed that the desirable odour of PFR increased feed palatability by improving ADFI [23]; however, such influence was not observed in the present study. The discrepancy might be caused by differences in freshwater fish source, batches, and storage duration, which influences the quality and nutritional composition of PFR.…”
Section: Growth Performancecontrasting
confidence: 98%
“…A further study is needed to clarify the adverse effect of long-term storage of PFR before use in livestock feed. A previous study revealed that the desirable odour of PFR increased feed palatability by improving ADFI [23]; however, such influence was not observed in the present study. The discrepancy might be caused by differences in freshwater fish source, batches, and storage duration, which influences the quality and nutritional composition of PFR.…”
Section: Growth Performancecontrasting
confidence: 98%
“…Then, we found YS supplementation resulted in a decrease of ST compared with piglets fed SS after 1 d of ST challenge, which was consistent with previous reports. 26 Expectedly, ST up-regulated this bacterium in excrement microflora during the late stage of challenge, indicating that the treated pigs may be successful in infection. Nowadays, overpopulation of E. coli might cause diarrhea and the inhibition of animal growth performance has been accepted.…”
Section: Discussionmentioning
confidence: 93%
“…However, several experiments have shown that YS supplementation reduced the fecal microflora in finishing pigs. 25,26 It was reported that piglets which were fed the yeast diet had limited effects on microbial counts in fresh feces. 27 The different results might be explained by the experimental animals, proper doses of YS, and types of YS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its small peptides can be readily absorbed in the small intestine. There have been several studies on nutritional values of fermented or hydrolyzed animal by-products to improve growth performance and nutrient digestibility [9][10][11]. Fermented fish meal was an effective protein ingredient to improve growth performance [9], and had higher apparent ileal digestibility of total AA than fish meal [11].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on nutritional values of fermented or hydrolyzed animal by-products to improve growth performance and nutrient digestibility [9][10][11]. Fermented fish meal was an effective protein ingredient to improve growth performance [9], and had higher apparent ileal digestibility of total AA than fish meal [11]. The hydrolyzed porcine intestinal mucosa product had similar to or greater degestible energy and metabolizable energy (ME) values than fish meal, and the standardized total track digestibility of phosphorus (P) was greater than fish meal [10].…”
Section: Introductionmentioning
confidence: 99%